Direct AC–AC grid interface converter for ocean wave energy system. (1st March 2015) - Tsang, K.M.; Chan, W.L.
Abstract : Graphical abstract: Highlights: Novel power grid interface converter for ocean wave energy system. Unlike conventional approach, generator output is directly converted into fixed frequency AC for synchronous connection. High conversion efficient and power quality could be achieved. Abstract: Ocean wave energy is very promising. However, existing systems are using rectifying circuits to convert variable voltage and variable frequency output of electric generator into DC voltage and then use grid-tied inverter to connect to the power grid. Such arrangement will not only reduce the overall efficient but also increase the cost of the system. A direct AC–AC converter is a desirable solution. In this paper, a six-switch AC–AC converter has been proposed as a single phase grid-connected interface. New switching scheme has been derived for the converter such that the virtual input AC–DC conversion and the output DC–AC conversion can be decoupled. State-space averaging model and pulse width modulation scheme have been derived for the converter. As the input and the output operations can be decoupled, two independent controllers have been designed to handle the input AC–DC regulation and the output DC–AC regulation. The proposed scheme demands for two separate duty ratios and novel switching scheme has been derived to realize the combined duty ratios in one switching cycle. Power regulation, harmonics elimination and power factor correction control algorithms have also been derived for the converter when it is connected to the supply grid. Experimental results of a small scale model are included to demonstrate the effectiveness of the proposed switching and control schemes.